Aberrant MicroRNA Expression in Patients With Endometrial Cancer. Issue 3 (March 2017) - Montagnana, Martina; Benati, Marco; Danese, Elisa; Giudici, Silvia; Perfranceschi, Melissa; Ruzzenenete, Orazio; Salvagno, Gian Luca; Bassi, Antonella; Gelati, Matteo; Paviati, Elisa; Guidi, Gian Cesare; Franchi, Massimo; et al.
Abstract : Objective: Current evidence suggests that no single serum biomarker displays satisfactory diagnostic performance in patients with endometrial carcinoma (EC), the most frequent gynecological cancer in developed countries. However, aberrant tissue microRNA (miRNA) expression has been recently described in EC. Therefore, this study aimed to investigate the differential expression of 4 serum miRNAs and their association with CA125 (cancer antigen 125) and HE4 (human epididymis protein 4) in EC patients and in a control population. Methods: Forty-six consecutive women with EC and 28 matched control subjects without a history of cancer or other diseases were enrolled. Total serum RNA was extracted using mirVana PARIS Kit. TaqMan MicroRNA Assay was used for quantitative real-time reverse transcriptase–polymerase chain reaction on ABI 7500 Sequence Detection System to assess differential miRNAs expression. The relative expression levels of 4 miRNAs (miR-222, miR-223, miR-186, and miR-204) were normalized to miR-16 and calculated using the 2-△Ct approach. Results: Serum levels of miR-186, miR-222, and miR-223 appeared to be significantly higher in patients compared with control subjects ( P = 0.004, P = 0.002, and P < 0.0001). Contrarily, serum miR-204 was found to be significantly lower in EC patients ( P < 0.0001). The diagnostic performance of miRNAs was found to be significantly better than that of CA125. Among the various biomarker tested, serum miR-204 and HE4 exhibited the best diagnostic performance for discriminating EC patients from control subjects. Conclusions: These results underpin that the 4 miRNAs that we have investigated are implicated in development and progression of EC, thus opening new avenues in EC diagnostics.